2020
DOI: 10.1016/j.ejca.2020.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Systematic target actionability reviews of preclinical proof-of-concept papers to match targeted drugs to paediatric cancers

Abstract: Background: Children with cancer are in urgent need of new therapies, as approximately 25% of patients experience a relapse and 20% succumb to their disease. Moreover, the majority of survivors suffer from clinically relevant health problems. Repurposing of targeted agents developed for adult indications could provide novel therapeutic options for paediatric cancer patients. To prioritise targeted drugs for paediatric clinical development, we applied a systematic review methodology to develop a Target Actionab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…This argues a strong case for the need to systematically review proof-of-concept (PoC) preclinical data to match paediatric tumour entities to the most promising therapeutic options. To address this, the target actionability review (TAR) methodology [6] was previously established as part of the innovative therapies for children with cancer paediatric preclinical PoC platform (ITCC-P4), an innovative medicines initiative 2-funded publiceprivate partnership between academic research institutions and pharmaceutical companies [7]. In a pilot TAR evaluating the MDM2-TP53 pathway in primary tumour data and preclinical models of paediatric cancers, we demonstrated that the TAR methodology provided the most comprehensive overview of available preclinical data on targeting of MDM2 in paediatric cancer to date [6].…”
Section: Introductionmentioning
confidence: 99%
“…This argues a strong case for the need to systematically review proof-of-concept (PoC) preclinical data to match paediatric tumour entities to the most promising therapeutic options. To address this, the target actionability review (TAR) methodology [6] was previously established as part of the innovative therapies for children with cancer paediatric preclinical PoC platform (ITCC-P4), an innovative medicines initiative 2-funded publiceprivate partnership between academic research institutions and pharmaceutical companies [7]. In a pilot TAR evaluating the MDM2-TP53 pathway in primary tumour data and preclinical models of paediatric cancers, we demonstrated that the TAR methodology provided the most comprehensive overview of available preclinical data on targeting of MDM2 in paediatric cancer to date [6].…”
Section: Introductionmentioning
confidence: 99%
“…The Pediatric Preclinical Testing Program (PPTP), sponsored by the US NCI, has been operating productively for several years, yielding dozens of publications on drug screens in various pediatric cancer models [ 47 ]. A European consortium formed the Innovative Therapy for Children with Cancer Paediatric Preclinical Proof-of-Concept Platform (ITCC-P4), a joint academic–pharmaceutical industry platform to characterize and prioritize targets in high-risk pediatric solid tumors [ 30 , 48 ] and facilitate tumor model development and drug screening. A pediatric preclinical public–private partnership is also being considered in the US [ 49 ].…”
Section: Key Recommendations: Preclinical/translationalmentioning
confidence: 99%
“…For drug targets not listed on the FDA’s relevant target list or the non-relevant target list (i.e., relevance not yet determined), the current FDA guidance provides a good outline of specific studies needed to establish relevance. In addition, Schubert et al recently published a more comprehensive framework of key experimental evidence for assessing target relevance and priority [ 48 ]. However, as the FDA is tasked with establishing relevance, it is unclear to what extent the sponsor is required to invest in such research.…”
Section: Key Recommendations: Preclinical/translationalmentioning
confidence: 99%
“…These are just a couple of the many reasons why industry is beginning to develop deeper ties with the pediatric research community. This deepening relationship is already contributing to advances in the understanding of target biology in pediatric cancers (e.g., "target actionability reviews"), 23 led to the development of an international consensus on the depth and breadth of preclinical data required for moving a promising agent into pediatric clinical development, 24 and resulted in the creation of precompetitive PPPs that bring academia and industry together to identify promising drugs for children dying from cancer. Of note regarding PPPs is the formal voice given to the critical but often overlooked contribution of patient advocacy, which plays a vital role in building bridges to all stakeholders while maintaining a patient focus.…”
Section: Setting the Stage For Industry Collaborationmentioning
confidence: 99%
“…ITCC-P4 has also established a methodology for the systematic in silico evaluation of selected compounds and corresponding actionable molecular targets and pathways in the different pediatric solid tumor entities (target actionability reviews) before the in vitro and in vivo testing phases to comprehensively assess relevant literature and the existing (epi)genomic and transcriptomic data sets of all entities in question. 23 To facilitate the design of preclinical packages for regulatory purposes, a joint ITCC-P4 and PPTC multistakeholder workshop with representatives from regulatory networks and industry, patient advocates, and academia established an international consensus on minimum preclinical testing requirements for the evaluation of compounds in pediatric oncology. 24 The ultimate goal is to deliver a sustainable high-quality preclinical testing platform with unique, fully characterized models and access to molecular information to serve the needs of both the biopharmaceutical industry as part of the new regulatory environment and the academic research community in an effort to continue to gain knowledge on pediatric malignancies and to drive pediatric oncology drug development through science in a much more rigorous and systematic way.…”
Section: Eu Perspective On Academia-industry Collaboration: Development and Status Of The Itcc-p4mentioning
confidence: 99%